Performance Evaluation of Wastewater Treatment of Different Industries - Rana, Megha (My University, 2014)
Industries generate moderately concentrated wastewater in huge volumes in terms of COD, BOD, TSS, TDS, phosphate, sulphate etc. It is not feasible to treat this wastewater in a single stage to meet the stipulated standards instead a combination of suitable treatments is required. The main objective of this paper was to perform a comparative study between secondary and tertiary treated sample characteristics from different industrial wastewater. Samples were collected from five industries in which two were STP, Two were textile industries and one was dairy industry. Characterization of samples was done and efficiency of all the parameter is calculated. Parameters like pH COD, BOD, TSS, TDS, phosphate concentration and sulphate concentration are estimated. Efficiency of all the parameters of industries was calculated. For trident group (textile industry) efficiency of TSS, TDS, COD, BOD, sulphate and phosphate concentration are, 52.84, 2.59, 59.09, 36.75, 7.74,16.66 %. For Raipur Kalan (STP) efficiency of pH, TSS, TDS, COD, BOD, sulphate and phosphate concentration are 10.97, 76.86, 8.11, 56.16, 79.91, 35.71,31.08 % respectively. For Radiant textiles (textile industry) efficiency of pH, TSS, TDS, COD, BOD, sulphate and phosphate concentration are 11.68, 60.23, 27.58, 10.98, 28.74, 5.85,12.5 % respectively. For Crown Milk (Dairy industry) efficiency of TSS, TDS, COD, BOD, sulphate concentration are 2.97, 23.59, 43.29, 6.15, 20.6, 9.41 % respectively. For Ludhiana (STP) efficiency of pH, TSS, TDS, COD, BOD, sulphate and phosphate concentration are 28, 4.37, 67.65, 74.86, 46.42, 36.95 % respectively.
MT, EST
Keywords: Performance; Wastewater; Treatment; Industries